AXIOLOGY OF SCIENCE: VALUES, FUNCTIONS, ETHICS OF SCIENCE - Muktasim Billah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research aims to explore the conceptual foundations of axiology in science, including how to optimally integrate moral values, ethics, and social commitment into the development of scientific disciplines. The approach employed includes a qualitative literature review to examine various sources discussing axiological principles, the role of science in society, and ethical principles for scientists. The primary analysis indicates that scientific knowledge grounded in moral and ethical values can foster sustainable and accountable innovation, while raising educational standards and research activities. The integration of moral and ethical values is essential for maintaining harmony between technological progress and social obligations, while simultaneously protecting the sustainability of nature and fostering a civilized community. However, the research also reveals that a number of educational and research institutions have not yet fully implemented these values, potentially leading to social and environmental harms. The study's conclusions emphasize the urgency of axiology as the primary foundation for building a balanced and responsible science. Therefore, further development research using a mixed-methods approach and emphasizing empirical data is recommended to further explore the application of axiology in science across diverse educational and research environments. With these steps, it is anticipated that scientific progress will proceed in a sustainable, dignified manner, and provide substantial benefits to the welfare of humanity and the surrounding ecosystem.